Pengujian Aplikasi Kasir dengan Metode Blackbox - Agus Baskoro Hidayat; Ruslan Abu Honi; Sinta Nuriyah; Surya Adji Pangestu; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The cashier application that is being built experiences obstacles and problems when logging in on the login page, when the user or user logs in entering password data and username results in data that cannot be validated into the application database. Thus the researcher performs the steps and stages of the testing process with the Balck Box method using the Equivalence Partition, with this Equivalence Partition being able to test the application in existing bug cases. This test is done by doing things that can be considered possible to become bugs or errors in the next application, with the Equivalence Partition stage through testing each page column field and each tested class. Then the results of the test successfully determine the success or failure of a cashier application in the process of using it as expected and test requirements.